Romance and the ozone layer: panel evidence on green behavior in couples - Anja Köbrich León; Janosch Schobin (Empirical Economics, 2022)
The exploration of the drivers of interpersonal alignment processes in romantic partners is particularly relevant to policies that promote green behavior because social anchoring in families and relationships can undermine effective behavioral change. The present paper aims to investigate the role important life events, such as childbirth, marriage, and the acquisition of real estate, in explaining the alignment of pro-environmental behavior within couples over time. The adoption of a life-course perspective is a novelty. We draw on a representative longitudinal panel data set to investigate the significance of important life events and the distribution of economic power within a relationship for green alignment. The empirical results are double edged. They show that partners who are expecting the birth of their first child are more similar than partners who are not expecting children. After childbirth, partners become significantly more dissimilar. Furthermore, we find evidence of a reconciliation effect. Over time, partners who divorce and continue cohabiting align more than partners who do not divorce.
Keywords: D10; D91; Q50; 330; Similarity; Environmental behavior; Couples; Life-cycle perspective; UKHLS